What influences healthcare professionals' treatment preferences for older women with operable breast cancer? An application of the discrete choice experiment. Issue 7 (July 2017) - Morgan, J.L.; Walters, S.J.; Collins, K.; Robinson, T.G.; Cheung, K.-L.; Audisio, R.; Reed, M.W.; Wyld, L.
Abstract: Introduction: Primary endocrine therapy (PET) is used variably in the UK as an alternative to surgery for older women with operable breast cancer. Guidelines state that only patients with "significant comorbidity" or "reduced life expectancy" should be treated this way and age should not be a factor. Methods: A Discrete Choice Experiment (DCE) was used to determine the impact of key variables (patient age, comorbidity, cognition, functional status, cancer stage, cancer biology) on healthcare professionals' (HCP) treatment preferences for operable breast cancer among older women. Multinomial logistic regression was used to identify associations. Results: 40% (258/641) of questionnaires were returned. Five variables (age, co-morbidity, cognition, functional status and cancer size) independently demonstrated a significant association with treatment preference (p < 0.05). Functional status was omitted from the multivariable model due to collinearity, with all other variables correlating with a preference for operative treatment over no preference (p < 0.05). Only co-morbidity, cognition and cancer size correlated with a preference for PET over no preference (p < 0.05). Conclusion: The majority of respondents selected treatment in accordance with current guidelines, however in some scenarios, opinion was divided, and age did appear to be an independent factor that HCPs considered when making a treatment decision in this population.